Penanganan Limbah Elektronik (E-Waste) di Indonesia Berbasis Seni dan Drop Point - R. Hilary A Yoga; Ningrum Suryaningsih; Andri Setia Prabowo; Joni Welman Simatupang (Fakultas Teknik, 2020)
Technological developments that increase the increase in electronic waste (e-waste) significantly. In Indonesia, the method of treating electronic waste by fire is not appropriate to apply, because electronic waste contains metals and will cause dangerous air pollution (for example: lead pollution). Electronic waste processing is different from organic waste that can be processed into fertilizer. Therefore, this condition can be categorized as an important problem, so it requires smart solutions that are fast and precise in processing. Handling this waste can be solved through several methods, namely e-waste banks and art integration. This method prioritizes artistic value, creativity, function, and in-depth knowledge of the waste, so that it can also take advantage of organizations or businesses that will bring profit and be environmentally friendly. This has also received support from the government through a program commonly known as Small and Medium Enterprises (UKM). The components that are usually buried, melted down, and destroyed will be sorted again based on their physicality so that it will facilitate the process of making art.